The EFFECT OF SOCIAL CAPITAL, FAMILY BUSINESS INNOVATION, AND DYNAMIC CAPABILITIES ON THE ORGANIZATIONAL AGILITY OF FAMILY BUSINESS - Agustiono Agustiono; Glenn Antonio (Prodi Ilmu Manajemen, Fakultas Ekonomi Universitas Muhammadiyah Cirebon, 2023)
The research is conducted to determine the effect of Social Capital (X1), Family Business Innovation (X2), and Dynamic capabilities (X3) on Organizational Agility (Y). The research is conducted using the quantitative method, applying the 5-Likert scale questionnaires to 180 Respondents who are family business members, by utilizing the purposive sampling method. This research utilizes multiple linear regression analysis to analyze the factors that provide significant effects on organizational agility. All three factors (Social Capital, Family Business Innovation and Dynamic capabilities) are reliable and valid according to the SPSS result after further calculation The result of the research presents the positive relationship and the significant impact that Social Capital, Family Business Innovation, and Dynamic Capabilities have on Organizational Agility in Family Businesses.